Description of Sarcocystis rauschorum sp. n. (Protozoa: Sarcocystidae) with experimental cyclic transmission between varying lemmings ( Dicrostonyx richardsoni ) and snowy owls ( Nyctea scandiaca ) - Cawthorn, Richard J.; Gajadhar, Alvin A.; Brooks, Ronald J. (Canadian Journal of Zoology, 1984)
Sarcocystis rauschorum sp. n. (Protozoa: Sarcocystidae) is heteroxenous, with varying lemmings (Dicrostonyx richardsoni) as expermental intermediate hosts and snowy owls (Nyctea scandiaca) as natural and experimental definitive hosts. Free sporocysts of a Sarcocystis-like organism (11.6 × 9.2 μm with a diffuse residuum of numerous small refractile granules) from intestinal scrapings of a naturally infected snowy owl were orally administered to laboratory-reared varying lemmings. Meronts were present 7 days post inoculation (DPI) in hepatocytes. Cysts of S. rauschorum sp. n. developed in striated muscle and contained metrocytes (4.6 × 3.8 μm) 14 DPI; bradyzoites (6 × 2 μm) were present at least as early as 28 DPI. Cysts at 84 DPI were not macroscopic (greatest diameter 80.9 μm, least diameter 70.9 μm) with walls 0.35–0.70 μm thick. Laboratory-reared rats (Rattus norvegicus), house mice (Mus musculus), white-footed mice (Peromyscus leucopus), red-backed voles (Clethrionomys gapped), and brown lemmings (Lemmus sibiricus) were not suitable intermediate hosts. Carcasses of varying lemmings containing cysts (57 and 84 DPI) of S. rauschorum sp. n. were fed to three Sarcocystis-free snowy owls. The prepatent period was 7 days and the patent period 12 – 19 days. Sporogony occurred in the lamina propria throughout the length of the small intestine. Free sporocysts (10.4 × 8.2 μm with a compact residuum of numerous small refractile granules) from experimentally infected owls were infective for varying lemmings.